Andre Hellegers and Carroll House: Architect and Blueprint for the Kennedy Institute of Ethics - Harvey, John Collins (Kennedy Institute of Ethics journal, 2004)
, The Newman programs established at secular colleges and universities provided an opportunity for intellectual, spiritual, and social growth among the Catholic student population. As a young physician and junior medical faculty member, André Hellegers took part in the early organization and ongoing work of Carroll House, the Newman Center at the Johns Hopkins Medical Institutions. Hellegers's experience at Carroll House enabled him to develop a clear blueprint of an academic center of excellence for the scientific, theological, and philosophical exploration of the many problems that he had seen and foresaw in medicine. That center would become Georgetown's Kennedy Institute of Ethics.